MELEGALKAN PERKAWINAN SESAMA JENIS DI INDONESIA? - Aryanata, Nyoman Trisna (Intuisi : Jurnal Psikologi Ilmiah, 2016)
Abstract. Lately appeared the issue of same-sex marriage in the Indonesian media that is triggered by the issue of foreign funds to support the existence of gays in Indonesia. Many parties issued their public statement in respond to the issue, including professional organizations in the field of psychiatry and psychology. This paper is going to discuss the issue of same-sex marriage through a review on the legal and socio-cultural aspects of homosexual existence and gay marriage in Indonesian context. The implications of gay marriage to the functioning of family will also be discussed.